Pemetaan Risiko Kekeringan Berbasis Integrasi Kemiringan Lereng dengan Sistem Informasi Geografis - Defwaldi Defwaldi; Dwi Marsiska Driptufani; Ilham Armi; Nasyahardian Nasyahardian (JURAL RISET RUMPUN ILMU TEKNIK, 2024)
Drought is a hydrometeorological disaster that significantly affects water availability and agricultural activities. Pesisir Selatan Regency has diverse topographic conditions that influence the level of vulnerability to drought, thereby requiring a comprehensive spatial analysis. This study aims to map drought risk by integrating slope steepness with other biophysical parameters using Geographic Information Systems (GIS). The data employed include slope maps derived from DEMNAS, rainfall data (CHIRPS 2024), soil types, land use, and river networks. The analysis was conducted through scoring and overlay methods to produce a drought risk map. The results indicate that areas with very steep slopes (>45%) have a high level of vulnerability due to surface runoff dominance and low infiltration capacity, particularly in Bayang Utara District. In contrast, flat to gently sloping areas dominated by rice fields and forest cover are relatively low-risk. Overall, drought risk in the region is classified into three categories: low, medium, and high. The resulting maps can serve as a basis for local governments in developing spatial planning policies, water conservation infrastructure, and disaster mitigation strategies that are more adaptive and sustainable.